Low internal stress low temperature curing epoxy reinforcing adhesive and preparation method thereof

CN122917718APending Publication Date: 2026-10-16KUNSHAN AINUOHUA ELECTRONIC MATERIALS TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611414365.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-11
Publication Date
2026-10-16

AI Technical Summary

Technical Problem

但填料的加入会增加体系粘度,影响操作性和对细微间隙的渗透能力;增韧剂若分散不良,不仅增韧效果受限,还可能劣化粘接强度

Benefits of technology

[0023] This invention provides a low-stress, low-temperature curing epoxy reinforcing adhesive and its preparation method. Through the synergistic combination of polyurethane-modified epoxy resin, a core-shell toughening agent, and spherical silica powder with appropriate particle size distribution, the epoxy reinforcing adhesive exhibits low internal stress characteristics (volume shrinkage ≤1.5% and CTE1 ≤40 ppm/℃) after curing at 60℃, effectively preventing interface cracking and component deformation. A stepwise mixing process, employing fine powder grinding followed by coarse powder addition, overcomes the bottleneck of filler dispersion difficulties at high filler contents, ensuring the adhesive's uniformity and workability. Furthermore, the core-shell toughening agent is introduced in the form of a pre-dispersed masterbatch, ensuring good dispersion of nano-scale toughening particles, resulting in significant toughening effects and controllable viscosity impact. The rational selection of the active hydrogen equivalent of the low-temperature curing agent, combined with the subsequent addition of the coupling agent, optimizes the cross-linking network structure and reduces curing shrinkage stress while ensuring rapid low-temperature curing.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The application belongs to the technical field of electronic adhesives, and particularly relates to a low-internal-stress low-temperature curing epoxy reinforcing adhesive and a preparation method thereof. The method comprises the following steps: S1, preparing a first premix; S2, uniformly mixing the first premix with a second part of spherical silica micropowder, and then adding a low-temperature curing agent and a curing accelerator, and stirring and defoaming under a vacuum degree to obtain a second premix; S3, adding a silane coupling agent to the second premix, and continuing to stir for 5-15 minutes under the same vacuum condition to obtain the low-internal-stress low-temperature curing epoxy reinforcing adhesive. Through the synergistic cooperation of the polyurethane modified epoxy resin, the core-shell toughening agent and the particle size graded spherical silica micropowder, the epoxy reinforcing adhesive has the low-internal-stress characteristics of a volume shrinkage rate ≤1.5% and CTE1 ≤40 ppm / ℃ after being cured at 60 DEG C, and effectively prevents the cracking of the bonding interface and the deformation of components.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of electronic adhesive technology, and particularly relates to a low-stress, low-temperature curing epoxy reinforcing adhesive and its preparation method. Background Technology

[0002] Epoxy resin adhesives are widely used in electronic packaging and assembly due to their high bonding strength, excellent heat resistance, and chemical resistance. Conventional epoxy adhesives typically require heating at temperatures above 100°C for an extended period to achieve sufficient crosslinking density and bonding strength. However, many electronic components, flexible circuits, or heat-sensitive substrates cannot withstand high-temperature baking, necessitating adhesives that can fully cure at lower temperatures around 60°C.

[0003] Lowering the curing temperature often results in higher curing shrinkage and internal stress. During curing, epoxy resin undergoes volume shrinkage, and the mismatch in thermal expansion coefficients between the cured product and the substrate causes thermal stress, easily leading to cracking at the bonding interface, component deformation, or circuit damage. To address this, existing technologies often add inorganic fillers to reduce the coefficient of thermal expansion and introduce toughening agents to absorb stress. However, the addition of fillers increases the system viscosity, affecting operability and penetration into fine gaps; if the toughening agent is poorly dispersed, not only is the toughening effect limited, but it may also deteriorate the bond strength. On the other hand, to adapt to low-temperature curing, highly reactive curing agents are usually selected. However, highly reactive curing agents have a short pot life after mixing with epoxy resin, and the curing crosslinking structure is difficult to control. A high crosslinking density results in a brittle cured product with concentrated internal stress, while a low crosslinking density leads to insufficient strength.

[0004] Therefore, how to significantly reduce the volume shrinkage and internal stress of the cured product while maintaining the ability to cure at low temperatures, and improve the dimensional stability and bonding reliability of the cured product, has become a technical problem that urgently needs to be solved in this field. Summary of the Invention

[0005] The main objective of this invention is to provide a low-stress, low-temperature curing epoxy reinforcing adhesive and its preparation method, so as to overcome the shortcomings of the prior art.

[0006] To achieve the aforementioned objectives, the technical solution adopted by this invention includes:

[0007] According to a first aspect of the present invention, a method for preparing a low-stress, low-temperature curing epoxy reinforcing adhesive is provided, comprising the following steps:

[0008] S1. At 15~35℃, 30~60 parts by weight of bisphenol A type epoxy resin, 5~20 parts by weight of polyurethane modified epoxy resin and 5~15 parts by weight of core-shell toughening agent are premixed, and the first part of spherical silica powder is added. The mixture is then ground and dispersed to a fineness of less than 15μm to obtain the first premix.

[0009] S2. Mix the first premix with the second part of spherical silica powder evenly, then add 10-25 parts by weight of low-temperature curing agent and 0.5-3 parts by weight of curing accelerator, and stir and degas for 10-30 minutes under a vacuum of -0.09 to -0.1 MPa to obtain the second premix.

[0010] S3. Add 0.1~1 parts by weight of silane coupling agent to the second premix, and continue stirring for 5~15 minutes under the same vacuum conditions to obtain the low internal stress low temperature curing epoxy reinforcing adhesive.

[0011] The weight ratio of the first part of spherical silica powder to the second part of spherical silica powder is 1:0.5~2, and the total amount of the two parts of spherical silica powder is 20~50 parts by weight; the low-temperature curing agent is a modified polythiol curing agent and / or a modified alicyclic amine curing agent, with an active hydrogen equivalent of 120~220 g / eq.

[0012] Furthermore, in step S1, the core-shell toughening agent is added in the form of a pre-dispersed masterbatch, which is composed of the core-shell toughening agent dispersed in bisphenol A type epoxy resin, and the mass fraction of the core-shell toughening agent in the pre-dispersed masterbatch is 30%~50%.

[0013] Furthermore, in step S1, the grinding and dispersion are carried out using a three-roll mill, and the material temperature is controlled to not exceed 40°C during the grinding process.

[0014] Furthermore, the low-temperature curing agent is a modified polythiol curing agent composed of polythiol and 2,4,6-tris(dimethylaminomethyl)phenol.

[0015] Furthermore, the polyurethane-modified epoxy resin is prepared by reacting polyether diol with diisocyanate to generate isocyanate-terminated prepolymer, and then adding it to bisphenol A type epoxy resin, with an epoxy equivalent of 250~400 g / eq.

[0016] According to a second aspect of the present invention, a low-stress, low-temperature curing epoxy reinforcing adhesive is provided, comprising, by weight: 30-60 parts of bisphenol A type epoxy resin; 5-20 parts of polyurethane modified epoxy resin; 5-15 parts of core-shell toughening agent; 20-50 parts of spherical silica powder; 10-25 parts of low-temperature curing agent; 0.5-3 parts of curing accelerator; and 0.1-1 parts of silane coupling agent; wherein the low-temperature curing agent is a modified polythiol curing agent and / or a modified cycloaliphatic amine curing agent;

[0017] The spherical silica powder is composed of a first spherical silica powder and a second spherical silica powder, with a weight ratio of 1:0.5~2. The average particle size D50 of the first spherical silica powder is 1~4 μm, and the average particle size D50 of the second spherical silica powder is 6~10 μm. After the epoxy reinforcing adhesive is cured at 60℃ for 2 hours, the volume shrinkage rate of the cured product is ≤1.5%, and the linear thermal expansion coefficient CTE1 is ≤40 ppm / ℃.

[0018] Furthermore, the core-shell toughening agent is an acrylate core-shell rubber particle with a particle size of 50~300 nm.

[0019] Furthermore, the epoxy equivalent of the polyurethane-modified epoxy resin is 250~400 g / eq.

[0020] Furthermore, the silane coupling agent is γ-glycidoxypropyltrimethoxysilane and / or γ-aminopropyltriethoxysilane.

[0021] Furthermore, the active hydrogen equivalent of the low-temperature curing agent is 120~220 g / eq.

[0022] Compared with the prior art, the advantages of the present invention include:

[0023] This invention provides a low-stress, low-temperature curing epoxy reinforcing adhesive and its preparation method. Through the synergistic combination of polyurethane-modified epoxy resin, a core-shell toughening agent, and spherical silica powder with appropriate particle size distribution, the epoxy reinforcing adhesive exhibits low internal stress characteristics (volume shrinkage ≤1.5% and CTE1 ≤40 ppm / ℃) after curing at 60℃, effectively preventing interface cracking and component deformation. A stepwise mixing process, employing fine powder grinding followed by coarse powder addition, overcomes the bottleneck of filler dispersion difficulties at high filler contents, ensuring the adhesive's uniformity and workability. Furthermore, the core-shell toughening agent is introduced in the form of a pre-dispersed masterbatch, ensuring good dispersion of nano-scale toughening particles, resulting in significant toughening effects and controllable viscosity impact. The rational selection of the active hydrogen equivalent of the low-temperature curing agent, combined with the subsequent addition of the coupling agent, optimizes the cross-linking network structure and reduces curing shrinkage stress while ensuring rapid low-temperature curing. Detailed Implementation

[0024] In view of the shortcomings of the prior art, the inventors of this invention, through long-term research and extensive practice, have proposed the technical solution of this invention. The following will further explain and illustrate this technical solution, its implementation process, and its principles.

[0025] The present invention will now be described in further detail with reference to specific embodiments. The given embodiments are merely illustrative of the invention and not intended to limit its scope. The embodiments provided below can serve as a guide for further improvements by those skilled in the art and do not constitute a limitation on the invention in any way.

[0026] Unless otherwise specified, the experimental methods used in the following embodiments are conventional methods, performed according to the techniques or conditions described in the literature in this field or according to the product instructions. Unless otherwise specified, the materials used in the following embodiments are commercially available.

[0027] This invention provides a method for preparing a low-stress, low-temperature curing epoxy reinforcing adhesive, comprising the following steps: S1, at 15~35℃, 30~60 parts by weight of bisphenol A type epoxy resin, 5~20 parts by weight of polyurethane modified epoxy resin and 5~15 parts by weight of core-shell toughening agent are premixed, a first part of spherical silica powder is added, and the mixture is ground and dispersed to a fineness of less than 15 μm to obtain a first premix;

[0028] S2. Mix the first premix with the second part of spherical silica powder evenly, then add 10-25 parts by weight of low-temperature curing agent and 0.5-3 parts by weight of curing accelerator, and stir and degas for 10-30 minutes under a vacuum of -0.09 to -0.1 MPa to obtain the second premix.

[0029] S3. Add 0.1~1 parts by weight of silane coupling agent to the second premix and continue stirring for 5~15 minutes under the same vacuum conditions to obtain low internal stress low temperature curing epoxy reinforcing adhesive.

[0030] In the above steps, the weight ratio of the first part of spherical silica powder to the second part of spherical silica powder is 1:0.5~2, and the total amount of the two parts of spherical silica powder is 20~50 parts by weight; the low-temperature curing agent is a modified polythiol curing agent and / or a modified alicyclic amine curing agent, and its active hydrogen equivalent is 120~220 g / eq.

[0031] This invention selects bisphenol A type epoxy resin as the main resin to provide basic adhesive strength and heat resistance; it introduces polyurethane-modified epoxy resin, whose molecular structure contains urethane segments, which can increase the flexibility of the cured network and reduce curing internal stress; at the same time, a core-shell toughening agent is used, in which the core-shell particles absorb energy through the cavitation and shear yielding of the rubber core during the curing process, effectively toughening the material without significantly reducing the glass transition temperature. The combination of these three components results in a good balance of rigidity and toughness in the cured product after low-temperature curing.

[0032] The addition of spherical silica powder employs a combination of stepwise feeding and particle size distribution: the first portion of fine-particle spherical silica powder is first ground together with resin and toughening agent in S1, utilizing high shear force to fully deagglomerate the fine powder and ensure good resin wetting, which helps improve filler dispersion uniformity and reduce system viscosity; the second portion of coarse-particle spherical silica powder is added in S2, utilizing the packing effect of coarse and fine particles to increase the filler volume filling rate, thereby effectively reducing curing shrinkage and thermal expansion coefficient. The weight ratio of the two portions of silica powder is limited to 1:0.5~2. If there is too much coarse powder, the packing voids are large, resulting in poor reinforcement and shrinkage reduction effects; if there is too much fine powder, the material viscosity is too high during grinding, which is not conducive to flow and penetration. The total dosage is 20~50 parts by weight. If it is too low, the effect of reducing internal stress is not obvious; if it is too high, the thixotropic nature of the adhesive is too strong, which is not conducive to the application process.

[0033] The low-temperature curing agent is limited to modified polythiol and / or modified alicyclic amine curing agents, with the active hydrogen equivalent controlled at 120~220 g / eq. This range ensures smooth curing initiation at 60℃, achieving a high functional group conversion rate, while avoiding excessive shrinkage stress due to excessively high crosslinking density. Adding the curing agent in S2 and degassing under vacuum effectively eliminates air bubbles introduced by stirring; in S3, a silane coupling agent is added, and stirring continues under vacuum to allow the coupling agent to spread evenly on the filler surface, undergo hydrolysis and condensation, and further remove air bubbles, preventing the coupling agent from prematurely participating in the main curing reaction and affecting the coupling effect.

[0034] To better understand the technical solution of the present invention, the following detailed discussion is provided in conjunction with specific embodiments.

[0035] Example 1

[0036] raw material:

[0037] 40 parts of bisphenol A type epoxy resin (E-51, epoxy equivalent 196 g / eq);

[0038] 10 parts of polyurethane modified epoxy resin (polyether diol-isophorone diisocyanate-epoxy adduct, epoxy equivalent 280 g / eq);

[0039] Core-shell toughening agent pre-dispersion masterbatch (acrylate core-shell rubber particles, particle size 150 nm, core-shell particle mass fraction in the masterbatch is 40%, the rest is E-51) 6 parts based on the effective component of core-shell particles, 15 parts of masterbatch actually weighed (including 9 parts of E-51).

[0040] 16 parts of spherical silica powder A (first spherical silica powder, D50=2 μm, maximum particle size 10 μm);

[0041] 12 parts of spherical silica powder B (second spherical silica powder, D50=8 μm, maximum particle size 22 μm); 18 parts of low-temperature curing agent (liquid polythiol and 2,4,6-tris(dimethylaminomethyl)phenol compounded at a mass ratio of 85:15, active hydrogen equivalent 160 g / eq);

[0042] Curing accelerator (2,4,6-tris(dimethylaminomethyl)phenol, DMP-30) 0.8 parts;

[0043] 0.5 parts of silane coupling agent (γ-glycidoxypropyltrimethoxysilane, KH-560);

[0044] This embodiment provides a method for preparing a low-stress, low-temperature curing epoxy reinforcing adhesive, comprising the following steps:

[0045] S1. At 25℃, 40 parts of E-51, 10 parts of polyurethane modified epoxy resin and 15 parts of core-shell toughening pre-dispersion masterbatch are premixed evenly, and 16 parts of spherical silica powder A are added. The mixture is then ground and dispersed to a fineness of <15 μm using a three-roll mill. During the grinding process, the material temperature is controlled to not exceed 40℃ to obtain the first premix.

[0046] S2. Add 12 parts of spherical silica powder B to the first premix, stir evenly, then add 18 parts of low-temperature curing agent and 0.8 parts of DMP-30, stir and degas for 20 minutes under a vacuum of -0.095 MPa to obtain the second premix.

[0047] S3. Add 0.5 parts of KH-560 to the second premix and continue stirring at -0.095 MPa for 10 minutes. Discharge the material to obtain epoxy reinforcing adhesive.

[0048] Curing conditions: 60℃ × 2 h. Properties: Volume shrinkage rate 1.2%, linear thermal expansion coefficient CTE 1 36 ppm / ℃, aluminum-aluminum shear strength 18.5 MPa.

[0049] Example 2

[0050] raw material:

[0051] Bisphenol A type epoxy resin (E-51) 30 parts;

[0052] 5 parts of polyurethane-modified epoxy resin (same as in Example 1);

[0053] Core-shell toughening agent pre-dispersion masterbatch (core-shell particle size 150 nm, core-shell particle mass fraction in the masterbatch 30%, the rest is E-51) 5 parts based on the effective component of core-shell particles, the actual weighed masterbatch 16.67 parts (including 11.67 parts of E-51).

[0054] 13.3 parts of spherical silica powder A (D50=2 μm);

[0055] Spherical silica powder B (D50=8 μm) 6.7 parts;

[0056] (The weight ratio of A to B is 1:0.5, and the total amount used is 20 portions)

[0057] 10 parts of low-temperature curing agent (same as in Example 1);

[0058] Curing accelerator (DMP-30) 0.5 parts;

[0059] 0.1 parts of silane coupling agent (KH-560);

[0060] This embodiment provides a method for preparing a low-stress, low-temperature curing epoxy reinforcing adhesive, comprising the following steps:

[0061] S1. At 20℃, 18.33 parts of E-51 (epoxy in the masterbatch has been deducted), 5 parts of polyurethane modified epoxy resin and 16.67 parts of core-shell toughening masterbatch are premixed, and 13.3 parts of spherical silica powder A are added. The mixture is then ground with three rollers until the fineness is <15 μm and the temperature is controlled at ≤40℃ to obtain the first premix.

[0062] S2. Add 6.7 parts of spherical silica powder B and mix well. Then add 10 parts of low-temperature curing agent and 0.5 parts of DMP-30. Stir and degas under a vacuum of -0.09MPa for 15 minutes to obtain the second premix.

[0063] S3. Add 0.1 parts of KH-560 and continue stirring at -0.09 MPa for 5 minutes, then discharge.

[0064] Curing conditions: 60℃ × 2 h. Properties: Volume shrinkage 1.5%, CTE 1 40 ppm / ℃, aluminum-aluminum shear strength 15.2 MPa.

[0065] Example 3

[0066] raw material:

[0067] Bisphenol A type epoxy resin (E-51) 60 parts;

[0068] 20 parts of polyurethane-modified epoxy resin (same as in Example 1);

[0069] Core-shell toughening agent pre-dispersion masterbatch (core-shell particle size 150 nm, core-shell particle mass fraction in the masterbatch 50%, the rest is E-51) 15 parts based on the effective component of core-shell particles, the actual masterbatch weighed is 30 parts (including 15 parts of E-51).

[0070] 16.7 parts of spherical silica powder A (D50=2 μm);

[0071] 33.3 parts of spherical silica powder B (D50=8 μm);

[0072] (The weight ratio of A to B is 1:2, and the total amount used is 50 portions).

[0073] Low-temperature curing agent (same as in Example 1) 25 parts;

[0074] Curing accelerator (DMP-30) 3.0 parts;

[0075] Silane coupling agent (KH-560) 1.0 part;

[0076] This embodiment provides a method for preparing a low-stress, low-temperature curing epoxy reinforcing adhesive, comprising the following steps:

[0077] S1. At 30℃, 45 parts of E-51 (epoxy in the masterbatch has been deducted), 20 parts of polyurethane modified epoxy resin and 30 parts of core-shell toughening masterbatch are premixed, and 16.7 parts of spherical silica powder A are added. The mixture is then ground with three rollers until the fineness is <15 μm and the temperature is controlled at ≤40℃ to obtain the first premix.

[0078] S2. Add 33.3 parts of spherical silica powder B and mix well. Then add 25 parts of low-temperature curing agent and 3.0 parts of DMP-30. Stir and degas under -0.1MPa vacuum for 30 minutes to obtain the second premix.

[0079] S3. Add 1.0 part of KH-560 and continue stirring at -0.1 MPa for 15 minutes, then discharge.

[0080] Curing conditions: 60℃ × 2 h. Properties: Volume shrinkage rate 0.9%, CTE1 30 ppm / ℃, aluminum-aluminum shear strength 21.3 MPa.

[0081] Comparative Example 1

[0082] The difference between the raw materials and those in Example 1 is that 16 parts of spherical silica powder A and 12 parts of spherical silica powder B are replaced with 28 parts of single-particle-size spherical silica powder (D50=8 μm, maximum particle size 22 μm), and all of them are added to the grinding process in S1. The rest of the formulation and steps are the same as in Example 1.

[0083] Test results: volume shrinkage rate 2.1%, CTE 1 55 ppm / ℃, aluminum-aluminum shear strength 14.3 MPa.

[0084] Results Analysis: The high porosity of single-size spherical silica powder resulted in ineffective compaction, leading to significantly higher solidification shrinkage and thermal expansion coefficients compared to Example 1, which used a coarse-fine gradation. Furthermore, the smaller total interfacial area between the single large-size filler and the resin reduced stress transfer efficiency and decreased bond strength.

[0085] Comparative Example 2

[0086] The raw materials are the same as in Example 1, the difference lies in the preparation process: in S1, 16 parts of spherical silicon micro powder A and 12 parts of spherical silicon micro powder B are added together to the mixture of resin and toughening agent, and then ground with three rollers until the fineness is <15 μm; in S2, no additional silicon micro powder is added, and the remaining steps are the same as in Example 1.

[0087] Test results: volume shrinkage rate 1.8%, CTE 1 48 ppm / ℃, aluminum-aluminum shear strength 15.6 MPa.

[0088] Results Analysis: Although the simultaneous addition of coarse and fine silica powders during grinding theoretically provides the necessary particle size distribution, the coarse powder undergoes high-intensity shearing during grinding, causing some spherical particles to break down. This disrupts the original particle size distribution and spherical morphology, resulting in a weakened gradation effect and a decrease in filler packing efficiency. Furthermore, when fine powder is ground together with coarse powder, the dispersion of the fine powder is not as thorough as that achieved with separate resin impregnation and grinding in a stepwise process. The filler agglomerates are not fully opened, leading to increased interfacial defects. Consequently, the shrinkage rate, CTE1, and strength are all lower than in Example 1.

[0089] Comparative Example 3

[0090] The difference between the raw materials and those in Example 1 is that 10 parts of polyurethane modified epoxy resin and 15 parts of core-shell toughening masterbatch (containing 6 parts of core-shell particles and 9 parts of E-51) are replaced with 25 parts of E-51, that is, the total amount of E-51 is adjusted to 65 parts. Flexible segments and core-shell particles are not introduced. The remaining components and steps are the same as in Example 1.

[0091] Test results: volume shrinkage rate 2.8%, CTE1 62 ppm / ℃, aluminum-aluminum shear strength 10.1 MPa.

[0092] Results Analysis: Removing the polyurethane-modified epoxy resin and the core-shell toughening agent increased the rigidity of the cured network. The lack of stress relaxation from flexible segments and the toughening and energy-absorbing effect of the core-shell particles led to a significant increase in curing shrinkage and thermal expansion, obvious internal stress concentration, and a significant decrease in bond strength. The test data from Comparative Example 3 indicate that the synergistic use of the polyurethane-modified epoxy resin and the core-shell toughening agent is key to achieving low internal stress and good bond performance.

[0093] Based on the data from the comparative examples and Example 1 above, it can be seen that the present invention, through the gradation of coarse and fine spherical silica powder and the stepwise feeding process, combined with the synergistic use of polyurethane modified epoxy resin and core-shell toughening agent, under the low-temperature curing condition of 60℃, reduces the volume shrinkage rate from 2.8% to 1.2%, the CTE1 from 62 ppm / ℃ to 36 ppm / ℃, and the aluminum-aluminum shear strength from 10.1 MPa to 18.5 MPa, with significant improvements in low internal stress effect and overall performance.

[0094] The above descriptions are merely some embodiments of the present invention. It should be noted that those skilled in the art can make other modifications and improvements without departing from the inventive concept of the present invention, and these all fall within the protection scope of the present invention.

Claims

1. A method for preparing a low-stress, low-temperature curing epoxy reinforcing adhesive, characterized in that, Includes the following steps: S1. At 15~35℃, 30~60 parts by weight of bisphenol A type epoxy resin, 5~20 parts by weight of polyurethane modified epoxy resin and 5~15 parts by weight of core-shell toughening agent are premixed, and the first part of spherical silica powder is added. The mixture is then ground and dispersed to a fineness of less than 15 μm to obtain the first premix. S2. Mix the first premix with the second part of spherical silica powder evenly, then add 10-25 parts by weight of low-temperature curing agent and 0.5-3 parts by weight of curing accelerator, and stir and degas for 10-30 minutes under a vacuum of -0.09 to -0.1 MPa to obtain the second premix. S3. Add 0.1~1 parts by weight of silane coupling agent to the second premix, and continue stirring for 5~15 minutes under the same vacuum conditions to obtain the low internal stress low temperature curing epoxy reinforcing adhesive. The weight ratio of the first part of spherical silica powder to the second part of spherical silica powder is 1:0.5~2, and the total amount of the two parts of spherical silica powder is 20~50 parts by weight; the low-temperature curing agent is a modified polythiol curing agent and / or a modified alicyclic amine curing agent, with an active hydrogen equivalent of 120~220 g / eq.

2. The preparation method according to claim 1, characterized in that, In step S1, the core-shell toughening agent is added in the form of a pre-dispersed masterbatch, which is composed of the core-shell toughening agent dispersed in bisphenol A type epoxy resin, and the mass fraction of the core-shell toughening agent in the pre-dispersed masterbatch is 30%~50%.

3. The preparation method according to claim 1, characterized in that, In step S1, the grinding and dispersion are carried out using a three-roll mill, and the material temperature is controlled to not exceed 40°C during the grinding process.

4. The preparation method according to claim 1, characterized in that, The low-temperature curing agent is a modified polythiol curing agent composed of polythiol and 2,4,6-tris(dimethylaminomethyl)phenol.

5. The preparation method according to claim 1, characterized in that, The polyurethane-modified epoxy resin is prepared by reacting polyether diol with diisocyanate to generate isocyanate-terminated prepolymer, and then adding it to bisphenol A type epoxy resin, with an epoxy equivalent of 250~400 g / eq.

6. A low-stress, low-temperature curing epoxy reinforcing adhesive, characterized in that, The raw materials for preparing the low-stress, low-temperature curing epoxy reinforcing adhesive include the following components in parts by weight: 30-60 parts of bisphenol A type epoxy resin; 5-20 parts of polyurethane modified epoxy resin; 5-15 parts of core-shell toughening agent; 20-50 parts of spherical silica powder; 10-25 parts of low-temperature curing agent; 0.5-3 parts of curing accelerator; 0.1-1 parts of silane coupling agent; wherein the low-temperature curing agent is a modified polythiol curing agent and / or a modified alicyclic amine curing agent; The spherical silicon micro powder is composed of a first spherical silicon micro powder and a second spherical silicon micro powder, with a weight ratio of 1:0.5~2. The average particle size D50 of the first spherical silicon micro powder is 1~4 μm, and the average particle size D50 of the second spherical silicon micro powder is 6~10 μm. After the epoxy reinforcing adhesive is cured at 60°C for 2 hours, the volume shrinkage rate of the cured product is ≤1.5%, and the linear thermal expansion coefficient CTE1 is ≤40 ppm / °C.

7. The low-stress, low-temperature curing epoxy reinforcing adhesive according to claim 6, characterized in that, The core-shell toughening agent is an acrylate-based core-shell rubber particle with a particle size of 50~300 nm.

8. The low-stress, low-temperature curing epoxy reinforcing adhesive according to claim 6, characterized in that, The epoxy equivalent of the polyurethane-modified epoxy resin is 250~400 g / eq.

9. The low-stress, low-temperature curing epoxy reinforcing adhesive according to claim 6, characterized in that, The silane coupling agent is γ-glycidoxypropyltrimethoxysilane and / or γ-aminopropyltriethoxysilane.

10. The low-stress, low-temperature curing epoxy reinforcing adhesive according to claim 6, characterized in that, The active hydrogen equivalent of the low-temperature curing agent is 120~220 g / eq.